1991
DOI: 10.1021/jo00004a048
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between solvation effects and mechanistic changes. Effects due to differences in solvation of aromatic rings and alkyl groups

Abstract: Solvolytic rate constants at 25 °C are reported for p-methoxybenzyl chloride (1) in aqueous binary mixtures with acetone, acetonitrile, dioxane, dimethyl sulfoxide, ethanol, methanol, and 2,2,2-trifluoroethanol and for benzoyl chloride and p-methoxybenzoyl chloride (2) in aqueous acetonitrile and aqueous dioxane. Product selectivities are reported for solvolyses of 1 in aqueous ethanol and methanol. Logarithms of rate constants for solvolyses of 2 correlate linearly with solvolyses of 1 (unit slope and only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
67
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 0 publications
3
67
0
Order By: Relevance
“…Solvent effects in binary trifluoroethanol (TFE) mixtures will be correlated with those for 1, Z = MeO to allow for the effects of solvent ionising power and of aromatic ring solvation. 7 It has recently been found that substituent effects for dissociative solvolyses of benzoyl chlorides correlate unexpectedly well with the original Hammett σ function. 8 The two types of correlation (for substituents and solvents) will provide the first independent estimates of the locations where each of the two pathways contributes 50% to the observed rate constant.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Solvent effects in binary trifluoroethanol (TFE) mixtures will be correlated with those for 1, Z = MeO to allow for the effects of solvent ionising power and of aromatic ring solvation. 7 It has recently been found that substituent effects for dissociative solvolyses of benzoyl chlorides correlate unexpectedly well with the original Hammett σ function. 8 The two types of correlation (for substituents and solvents) will provide the first independent estimates of the locations where each of the two pathways contributes 50% to the observed rate constant.…”
Section: Introductionmentioning
confidence: 96%
“…4 Recent DFT calculations indicate that the rate enhancing effects of both electron-donating and electronwithdrawing substituents on solvolyses of acid chlorides (1) in water can be explained by a concerted S N 2 mechanism along with large changes in transition state structure. 5 The purpose of our study is to provide further experimental evidence for the alternative mechanistic explanation 6,7 of simultaneous (concurrent) reaction pathways. Solvent effects in binary trifluoroethanol (TFE) mixtures will be correlated with those for 1, Z = MeO to allow for the effects of solvent ionising power and of aromatic ring solvation.…”
Section: Introductionmentioning
confidence: 97%
“…Koo et al have analyzed the solvolytic rate constants and product selectivities ( S ) of cinnamyl chloride [23] and cinnamyl bromide [24] in a number of binary mixtures of water with ethanol, methanol, acetone, and 2,2,2-trifluoroethanol (TFE). The close similarity of solvent kinetic isotope effects, rate-rate profiles of solvent effects on reactivity, and similar selectivity data to p -methoxybenzyl chloride [11, 25] made the authors conclude that the solvolyses of cinnamyl halides can be explained by product formation incorporating a general base-catalyzed nucleophilic attack on a contact ion-pair [23, 24]. Cinnamyl bromide was subject to electrochemical reduction using cyclic voltammetry and controlled-potential electrolysis [26] where it was shown that the substrate could be reduced to a resonance-stabilized cinnamyl radical, which could further be reduced to a carbanion depending upon the selected potential.…”
Section: Introductionmentioning
confidence: 97%
“…Bentley et al [11] favored the use of p -methoxybenzyl chloride as a similarity model to correlate the solvolyses of α -aryl halides. Liu et al [12, 13] also using a similarity model approach developed Y BnX scales for each leaving group X and Y x BnX scales [14] for x aromatic rings entering into conjugation with the reaction center.…”
Section: Introductionmentioning
confidence: 99%
“…We have carried out further work because the results reported were obtained using only 18 solvents for the correlation analysis; in particular, the experimental results were obtained without considering highly aqueous solvent systems including aqueous 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP), which may influence those of 4 by inducing a mechanistic change [6][7][8][9] due to the variation of solvent composition; also, there is a potential problem of possible multicolinearity for solvolytic analyses by two-terms multiple regressions.…”
Section: Introductionmentioning
confidence: 99%